DYNAMICS OF FOUR CIRCULAR SOLIDS SEDIMENTATION USING LATTICE BOLTZMANN-IMMERSED BOUNDARY METHOD - Adina Restu, Anastiara
This study presents numerical simulation on solid motion in viscous fluid column based on Lattice Boltzmann-Immersed Boundary method with modified spreading operator where IB method is employed to include solid as moving boundary. Simulation in this study is the dynamics of four solids and this study observes how the initial configuration effects the dynamics when solids sediment. The procedure of this coupled method is IB force is calculated from fluid macroscopic velocity on IB points. The initial configuration arrangements were varied to observe the solid position to drag force which shown by vertical velocity and trajectory plot. The result shows that drag force of a solid is affected by amount of geometry boundaries such as walls and other solids around the solid.